2017
DOI: 10.1016/j.jalgebra.2017.01.042
|View full text |Cite
|
Sign up to set email alerts
|

A non-Golod ring with a trivial product on its Koszul homology

Abstract: Abstract. We present a monomial ideal a ⊂ S such that S/a is not Golod, even though the product in its Koszul homology is trivial. This constitutes a counterexample to a well-known result by Berglund and Jöllenbeck (the error can be traced to a mistake in an earlier article by Jöllenbeck).On the positive side, we show that if R is a monomial ring such that the rary Massey product vanishes for all r ≤ max(2, reg R − 2), then R is Golod. In particular, if R is the Stanley-Reisner ring of a simplicial complex of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 24 publications
(23 reference statements)
0
30
0
Order By: Relevance
“…In [66], Golod showed that (13.1) holds if and only if all products and all higher Massey products vanish in Tor S (R, K), (see also [89]). Higher Massey products in H * (X; Q) obstruct the rational formality of X.…”
Section: Polyhedral Products and The Golodness Of Monomial Ideal Ringsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [66], Golod showed that (13.1) holds if and only if all products and all higher Massey products vanish in Tor S (R, K), (see also [89]). Higher Massey products in H * (X; Q) obstruct the rational formality of X.…”
Section: Polyhedral Products and The Golodness Of Monomial Ideal Ringsmentioning
confidence: 99%
“…Remark. According to [89] and [66], Serre had observed that the coefficients on the left hand side in (13.1) are always less than or equal to the corresponding coefficients on the right.…”
Section: Polyhedral Products and The Golodness Of Monomial Ideal Ringsmentioning
confidence: 99%
“…It is well-known that, for homogeneous ideals inside polynomial rings in three variables, being Golod is equivalent to requiring that the product on the Koszul homology is trivial (for instance, see [15,Theorem 6.3]). In the same article, it is shown that this is not the case more generally, even for monomial ideals.…”
Section: Characterization Of Monomial Golod Ideals In Three Variablesmentioning
confidence: 99%
“…The notion is defined and studied extensively in the local setting, but in this paper we shall restrict ourselves to the graded situation. Golod rings and ideals have attracted increasing attention recently (see [6,8,9,12,15]), but they remain mysterious even when n = 3. For instance, we do not know if the product of any two homogeneous ideals in Q = k[x, y, z] is Golod.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalence between the second and third statement of Theorem 6.5 is known. See for example Lemma 2.4 of [18] Example 6.7. Let S = k[x 1 , .…”
Section: The Ring R Is Gcdmentioning
confidence: 99%